OPPORTUNITIES FOR USING INNOVATIVE SOFTWARE TOOLS IN DEVELOPING METHODOLOGICAL COMPETENCE OF FUTURE BIOLOGY TEACHERS - Salimova Sarvinoz Farxodovna; Shamsiyeva Shaxzrizabonu Rustamovna (Web of Journals Publishing, 2025)
This article analyzes the role of innovative software educational tools in the formation and development of methodological competence of future biology teachers, their capabilities, advantages and effectiveness. It also highlights the role of modern web platforms and interactive resources in the educational process.
Keywords: Methodological competence, innovative software tools, biology education, digital platforms, teacher training.